Answer:
-8
Step-by-step explanation:
let the other number be x
according to the question equation is
-12x = 96
x = 96/-12
x = -8
Answer:
A
(hg)( x)=(4x-3)(x+2)=4x²+5x-6
Answer:
or 3.61
Step-by-step explanation:
Draw a right triangle and use the Pythagorean Theorem to find the hypotenuse, using the given points to find the length of the two sides. See the attachment.
<span>The value of (a-1)+a^2-b^2/1-ab+2(a-b)/2b when a=2 and b=-1 will be evaluated as follows:
substituting the values in the expression we obtain:
(2-1)+2^2-(-1)^2/1-(2*(-1))+2(2-(-1))/(2(-1))
simplifying the above we get:
1+4-1/1-(-2)+2(2+1)/(-2)
=1+4-1+2(3)/(-2)
=1+4-1-3
=5-4
=1
Answer: 1</span>